2018
DOI: 10.1016/j.immuni.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The Pore-Forming Protein Gasdermin D Regulates Interleukin-1 Secretion from Living Macrophages

Abstract: The interleukin-1 (IL-1) family cytokines are cytosolic proteins that exhibit inflammatory activity upon release into the extracellular space. These factors are released following various cell death processes, with pyroptosis being a common mechanism. Recently, it was recognized that phagocytes can achieve a state of hyperactivation, which is defined by their ability to secrete IL-1 while retaining viability, yet it is unclear how IL-1 can be secreted from living cells. Herein, we report that the pyroptosis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
836
2
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 894 publications
(898 citation statements)
references
References 29 publications
47
836
2
13
Order By: Relevance
“…The decision between killing the cell or allowing IL-1β secretion might depend on the strength of the signal that promotes inflammasome activation and gasdermin D processing. According to Evavold’s study, pyroptosis and IL-1β release can be uncoupled under “cell hyperactivation”[53]; therefore, we can conclude that B cells infected with Salmonella ΔsopB achieve a state of hyperactivity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The decision between killing the cell or allowing IL-1β secretion might depend on the strength of the signal that promotes inflammasome activation and gasdermin D processing. According to Evavold’s study, pyroptosis and IL-1β release can be uncoupled under “cell hyperactivation”[53]; therefore, we can conclude that B cells infected with Salmonella ΔsopB achieve a state of hyperactivity.…”
Section: Discussionmentioning
confidence: 87%
“…This autoregulated protein is responsible for pyroptosis and is active only when processed by caspase-1 or caspase-11 [51,52]. However, recent reports have described gasdermin D processing and the formation of membrane pores to allow IL-1β secretion without inducing pyroptosis [53,54]. The decision between killing the cell or allowing IL-1β secretion might depend on the strength of the signal that promotes inflammasome activation and gasdermin D processing.…”
Section: Discussionmentioning
confidence: 99%
“…Gasdermin‐D is activated by caspase‐1 and forms pores in the membrane, which leads to cell death . It has been recently proposed that IL‐1 β and IL‐18 release happens through gasdermin‐D pores; even so, further research is needed. Gasdermin‐D is also expressed in epithelial cells, and its involvement on inflammasome activity has been reported.…”
Section: The Inflammasome: a Well‐regulated Immune Platform Also Presmentioning
confidence: 99%
“…This would show that gasdermin‐D is functional and important for epithelial cell inflammasome function. Interestingly, in recent years, it has been reported that under certain circumstances the release of pro‐inflammatory cytokines and cell death are uncoupled upon inflammasome activation in several cell types such as neutrophils, monocytes and macrophages . This is particularly important for epithelial cells where the conservation of the integrity of the epithelial layer is key to maintain barrier homeostasis (Fig.…”
Section: The Inflammasome: a Well‐regulated Immune Platform Also Presmentioning
confidence: 99%
“…Clustering of pro-caspase-1 molecules leads to proximity-induced auto-proteolysis into p20 and p10 subunits, which in turn cleave pro-IL-1b to generate active IL-1b (Dinarello, 1998). Suggested mechanisms include exocytosis via secretory lysosomes (Andrei et al, 1999(Andrei et al, , 2004, secretion by microvesicle shedding (MacKenzie et al, 2001), release of multivesicular bodies that may contain exosomes (Qu et al, 2007), an autophagy-based secretory pathway (Dupont et al, 2011), gasdermin D-dependent secretion via pores (Evavold et al, 2018) and a loss of membrane integrity leading to passive IL-1b release that occurs in parallel with pyroptotic death of the secreting cell (Shirasaki et al, 2014;Martin-Sanchez et al, 2016). Ever since an alternative secretory pathway for the leaderless IL-1b has been reported (Rubartelli et al, 1990), the exact manner of release remains matter of debate.…”
Section: Introductionmentioning
confidence: 99%